2017
DOI: 10.3791/56409
|View full text |Cite
|
Sign up to set email alerts
|

Live Images of GLUT4 Protein Trafficking in Mouse Primary Hypothalamic Neurons Using Deconvolution Microscopy

Abstract: Type 2 diabetes mellitus (T2DM) is a global health crisis which is characterized by insulin signaling impairment and chronic inflammation in peripheral tissues. The hypothalamus in the central nervous system (CNS) is the control center for energy and insulin signal response regulation. Chronic inflammation in peripheral tissues and imbalances of certain chemokines (such as CCL5, TNFα, and IL-6) contribute to diabetes and obesity. However, the functional mechanism(s) connecting chemokines and hypothalamic insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The housing of mice and the animal for primary neuronal cell isolation were performed in accordance with protocols approved by the Institutional Animal Care and Use Committees of the Taipei Medical University (Protocol numbers: LAC-2015-0397; LAC-2019-0020). Primary neurons were cultured from mice embryos at day 16.5 (E16.5–E17.5), as described previously . In short, dishes were coated with poly l -lysine (Sigma-Aldrich, USA) overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The housing of mice and the animal for primary neuronal cell isolation were performed in accordance with protocols approved by the Institutional Animal Care and Use Committees of the Taipei Medical University (Protocol numbers: LAC-2015-0397; LAC-2019-0020). Primary neurons were cultured from mice embryos at day 16.5 (E16.5–E17.5), as described previously . In short, dishes were coated with poly l -lysine (Sigma-Aldrich, USA) overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Primary neurons were cultured from mice embryos at day 16.5 (E16.5−E17.5), as described previously. 38 In short, dishes were coated with poly L-lysine (Sigma-Aldrich, USA) overnight. Pregnant mice were sacrificed by CO 2 intoxication and the embryos were separated from the embryonic sac.…”
Section: Pcs and Preparation Of Hpls The Institutional Reviewmentioning
confidence: 99%
“…Pregnant mice at embryonic day 16–17 (E16-E17) were euthanized after being anesthetized with high-dose Avertin (400 mg/kg). Embryonic hypothalamic regions were dissected from brains on ice-cold DPBS immediately as a previous protocol described [31]. Hypothalamic tissues were digested with EDTA Trypsin (0.125%, Gibco) at 37 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Changou et al [71] reported a detailed protocol for another cell type in GLUT4 insulin signal regulation research, primary hypothalamic neurons. They applied GFP-GLUT4 protein to track GLUT4 membrane translocation upon insulin stimulation.…”
Section: General Labeling Strategies For Glut4 Visualization By Tradi...mentioning
confidence: 99%